Severe community-acquired pneumonia caused by Chlamydia psittaci genotype E/B strain circulating among geese in Lishui city, Zhejiang province, China. Issue 1 (31st December 2022) - Qin, Xin-Cheng; Huang, Jinwei; Yang, Zhangnv; Sun, Xiangrong; Wang, Wen; Gong, Enhui; Cao, Zhuo; Lin, Jianfeng; Qiu, Yanai; Wen, Bohai; Kan, Biao; Xu, Jianguo; et al.
ABSTRACT: Between November 2021 and January 2022, four patients of community-acquired pneumonia were admitted to the hospitals in Lishui city, Zhejiang province, China. Their main clinical manifestations were fever and dry cough as well as radiographic infiltrate, but the empiric antimicrobial therapy or traditional Chinese medicine was not effective for their illness. Clinical specimens from the patients as well as environmental and poultry specimens were collected for the determination of the causative pathogen. The ompA gene and seven housekeeping genes of Chlamydia psittaci were successfully amplified from all the patients, and the sequences of each gene were identical to one another, suggesting that they were infected by the same strain of C. psittaci . A novel strain of C. psittaci (LS strain) was isolated from the bronchoalveolar lavage fluid of patient 2 and its whole genome was obtained. Phylogenetic analyses based on the whole-genome sequences showed that the isolate is most closely related to the strain (WS/RT/E30) identified as genotype E/B. In addition, The ompA gene and four housekeeping genes of C. psittaci were also amplified from two of four faeces samples of geese at the home of patient 2, and the sequences from geese were 100% identical to those from the patients. Accordingly, these cases could be attributed to a circulating C. psittaci strain of genotype E/B in the local geese. Therefore, there is an urgent need to strengthen the regional surveillance on C. psittaci among poultry and humans for prevention and control of the outbreak of psittacosis in the city.